Cross-Sectional Study on Nurses' Attitudes toward Organ Donation: A Comparison of Two Hospitals from Greece. - Kalli, Antonia; Lamnisos, Dimitris; Andrea-Apostolidou, Stavroula (International Journal of Caring Sciences)
Background: The limited supply of organs for transplantation is an important inhibitory factor in promoting transplant programs. The positive attitude of the health professionals as well as the potential donor family towards transplants can greatly contribute to the increase in organ donation. Educating younger age health professionals may be a catalyst in promoting transplantation. Objective: Investigate the attitudes and opinion of nurses to the issue of organ donation and their possible correlations with demographic characteristics Methodology: A cross-sectional study was conducted with a convenience sample of 103 Nurses working in Intensive Care Units and Nephrology Department (Hemodialysis) in Greece from June to August 2018. In order to investigate the attitude of nurses the Flodén Attitudes Toward Organ Donor Advocacy Instrument (ATODAI) questionnaire was used. Results: Analysis shows that nurses in a great extent are willing to secure the wishes of the potential organ donor, to support the family of potential organ donors and promoting organ donation for the two Greek hospitals. Conclusions: The role of nurses is crucial in the transplantation process as it is a factor that can determine the choices of patients' relatives regarding the decision to donate organs for transplantation. Nurses can be the key to the success or failure of transplantation programs as they can influence, either positively or negatively, patients 'relatives to decide on organ donation in cases where they do not know the patients' views.